The development of a design methodology for large cargo aircraft - Mederer, A. (Cranfield University, 2008)
Detailed specialist knowledge of pre-design, design, aerodynamics, engine performances and flying performances is necessary for the pre-design of transport aeroplanes. In this paper, studies are described which provide the main detailed information on the above-mentioned specialist topics. All studies consists of a problem with a suitable solution and the associated results. The studies are part of the overall task “Systematic design study on a number of configurations for large aircraft types, in particular for cargo aeroplanes”. As part of the overall task, a design method was developed which is very user-friendly and which is suitable for the design of any aeroplane configurations, in particular for configurations of large passenger or transport aeroplanes. This thesis version shows how 11 transport aeroplane configurations of very different types can be drawn up. The configuration results are shown on a scale of 1 : 500 and can be directly used for more detailed studies, as they are based on calculations. 4 of the first 5 transport aeroplane configurations are basic configurations and were scaled between 200 to 10001 . Important flying performance characteristics were calculated for the configurations by the use of 8 PC programs additionally developed for this purpose. Validity studies have shown that the described design method provides useful results. The main result of the method is that very different transport aeroplane versions can be developed and compared in terms of flying performances. Currently, only a few very complex design methods are offered elsewhere which have the disadvantage that they are only intended for one aeroplane version. So far, the design method described in this method is fully applied to the first five configurations. A next step could be to also investigate the additional six configurations listed here with the method.